FUTURE STAYING PREFERENCES OF YOUTH MIGRANTS: CASE OF SLEMAN DISTRICT, SPECIAL REGION OF YOGYAKARTA - Meirina Ayumi Malamassam (Jurnal Kependudukan Indonesia, 2017)
The 2010 Indonesia census report shows that about 30 percent of the internal migrant population belongs to youths aged between 15 and 24 years old. A substantial proportion of the young migrants moves to pursue tertiary education. It is important to examine the spatial dynamics of the graduate youth migrants since their presence in an area can represent the provision of economic opportunity as well as acceleration of economic growth and investment. This study analysed data from the ‘Youth Migration in Indonesia’ survey by the Research Center for Population, Indonesian Institute of Sciences (2016) which was conducted in Sleman district, Special Region of Yogyakarta, one of the prominent destination areas for college student migrants within Indonesia. It is found that about one-third of the migrants intend to remain in their current residential city, and the rest express their intention to re-migrate, either returning to their hometowns or moving to new areas. The demographic and spatial attributes of the youths of the migrants are related to their future staying preferences. The findings also suggest that critical motivations for future migration by the educated migrants are employment situations, social ties, and urban facilities.